Inclusive Curriculum Reform in Multicultural Education Systems: Rethinking Policy and Leadership for Educational Equity - Raveenthiran Vivekanantharasa; Moses Adeleke Adeoye; Uthman Shehu Lawal (Edu Spectrum: Journal of Multidimensional Education, 2026)
This study examines the role of inclusive curriculum reform in promoting educational equity within multicultural education systems. The research focuses on the interconnected roles of curriculum transformation, educational policy, and transformative leadership in fostering inclusive and socially just learning environments. Using a qualitative content analysis approach, the study analyzed scholarly articles, policy documents, educational reports, and academic literature related to multicultural education, inclusive pedagogy, leadership, and equity-oriented policies. The findings reveal that inclusive curriculum reform serves as a fundamental strategy for recognizing cultural diversity, reducing discrimination, and enhancing equal participation among students from diverse backgrounds. Furthermore, effective educational policies and transformative leadership practices were identified as essential factors in supporting sustainable inclusive educational reform. However, the study also found that the implementation of inclusive curriculum reform continues to face significant challenges, including inadequate teacher preparation, limited institutional resources, policy inconsistency, technological inequality, and sociocultural resistance